Oxidative stress, endothelial dysfunction, cytokine imbalance, gonadotropic synergism, or all about tocopherol in the practice of an obstetrician-gynecologist - E. M. Dzhobava (IRBIS LLC, 2018)
Generation of reactive oxygen species (ROS) occurs in every human. The condition of oxidative stress develops when the human antioxidant defenses including the enzymes superoxide dismutase, peroxidases etc., and biological antioxidant molecules, are insufficient. Vitamin E is part of the antioxidant family. It plays a key role in neutralizing ROS, and its scope of activity ranges from the inhibition of heme biosynthesis and lipid peroxidation to maintaining the collagen/elastin balance. Vitamin E deficiency may be either primary or secondary; both shift the balance towards the development of oxidative stress, which may affect the normal course of pregnancy. As a result, pregnancy loss or preterm birth may ensue. Moreover, the oxidative stress can have a negative impact on the development of a fetus. In addition, the oxidative stress may play a role in various female reproductive disorders, eventually leading to infertility. In the today's world, the popular commitment to low-cholesterol and low-fat diets often leads to an increasing number of women with vitamin E deficiency. In order to maintain normal pregnancy, this imbalance requires an adequate correction starting at the stage of preconception care.